Adaptive plasticity of Laguncularia racemosa in response to different environmental conditions: integrating chemical and biological data by chemometrics - da Souza, Lara (2014)
Mangroves are dynamic environments under constant influence of anthropic contaminants. The correlation between environmental contamination levels and possible changes in the morphology of plants, evaluated by multivariate statistics helps to highlight matching between these variables. This study aimed to evaluate the uptake and translocation of metals and metalloids in roots and leaves as well as the changes induced in both anatomy and histochemistry of roots of Laguncularia racemosa inhabiting two estuaries of Espírito Santo (Brazil) with different pollution degrees. The analysis of 14 elements in interstitial water, sediments and plants followed by multivariate statistics, allowed the differentiation of studied sites, showing good match between levels of elements in the environment with the corresponding in plants. L. racemosa showed variations in their root anatomy in different collection areas, with highest values of cortex/vascular cylinder ratio, periderm thickness and air gap area in Vitória Bay, the most polluted sampling area. These three parameters were also important to differentiate the mangrove areas by linear discriminant analysis. The development stage of aerenchyma in roots reflected the oxygen availability in the water, being found a negative correlation between these variables. The combined use of chemical and biological analyses responded quite well to different pollution scenarios, matching morphological responses to physical and chemical parameters, measured at different partitions within the estuary. Thus, L. racemosa can be confirmed as a reliable sentinel plant for biomonitoring of estuaries impacted by anthropic pollution.